Eksplorasi Nilai-Nilai Luhur dalam Tradisi Lisan “Berasan” Adat Perkawinan Kota Bengkulu - Eli Diana (Universitas Mulawarman, 2023)
In living their social life, humans are bound by various life guidelines to create harmony between communities. One can be taken from the values contained in literary works traditionally maintained among the community, such as oral traditions. This study aims to describe the oral tradition in the Berasan event, a consensus deliberation event by Bengkulu city community leaders preparing for marriage, and explain its noble values as guidelines in social life. Using the descriptive qualitative method, the main data in this research is obtained from sentences delivered by Berasan participants in the form of conversation using the Bengkulu local language. The data was collected directly by listening to the Berasan event, interviewing the customary leader, and using the customary leader's unpublished personal documents. The results showed that the Berasan event is full of figurative sentences, namely rhymes, and proverbs, to convey intentions and goals. While the noble values implied in it include: religious values, humility, unity, empathy, and firmness. It needs to be preserved to maintain the stability of social relations in the Bengkulu city community.